(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the symbolic function of childhood as a marker of cultural identity in modern Uzbek and English literature. Using a comparative qualitative approach, the study analyzes selected works from contemporary Uzbek prose and English fiction, focusing on how child figures embody social memory, moral values, trauma, and transformation. Texts by O‘tkir Hoshimov, Hamid Ismailov, Charles Dickens, and Ian McEwan are comparatively examined to reveal how childhood operates as a cultural metaphor. The findings demonstrate that while Uzbek narratives often portray childhood as a vessel of collective memory and moral continuity, English narratives more frequently depict it as a site of psychological complexity and social critique. The study concludes that childhood symbolism reflects broader cultural frameworks, historical experiences, and narrative traditions in both literatures.